A Salicylic Acid-Binding Activity and a Salicylic Acid-Inhibitable Catalase Activity Are Present in a Variety of Plant Species. - Sanchez-Casas, P. (1994)
Recently, it has been demonstrated that the salicylic acid (SA)-binding protein (SABP) from tobacco (Nicotiana tabacum) is a SA-inhibitable catalase (Z. Chen, H. Silva, D.F. Klessig [1993] Science 262: 1883-1886). Here we report the presence of SABP and SA-inhibitable catalase activity in Arabidopsis, tomato, and cucumber. The cucumber SABP has properties similar to the tobacco SABP, including binding affinity and specificity for SA.